CCAFS Climate Smart Cocoa Baseline Survey Report-Ghana (Introduction of stepwise climate smart cocoa practices to farmers) - Dalaa, Mustapha Alasan; Saeed, Abdul-Razak; Deffor, Eric Worlanyo; Holzer, Manuel; Kofituo, Rich Kofi; Asare, Richard (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The International Institute of Tropical Agriculture (IITA) and the Rainforest Alliance (RA) have developed improved practices for climate-smart agriculture in the cocoa sector, summarized under the term climate-smart cocoa (CSC) and is carried out as part of the CGIAR research program on Climate Change, Agriculture and Food Security (CCAFS). In phase 1 of the CCAFS project on CSC, climate exposure maps for Ghana’s cocoa sector and site-specific recommendations for climate-smart agricultural practices were developed and adopted in 2019 the Ghana COCOBOD as a basis for the creation of a national climate-smart cocoa standard. Furthermore, a stepwise investment pathway towards CSC was developed to provide farmers with tangible investment packages allowing them to optimize their resource use. This novel approach to climate resilience, adaptation, and mitigation has a high potential to foster sustainable cocoa production in Ghana while positively impacting farmers’ livelihoods. This approach can also serve as a model for other crops in the region. The current challenge is to mainstream the CSC practices across the sector because the cocoa industry struggles to institutionalize CSA packages in training programs of companies and certification bodies. In addition to that, more data on the stepwise approach for climate-smart cocoa is needed to be able to establish a business case for CSA investment in both, the adjust and cope zone. These challenges are being addressed in phase II of the CCAFS project on climate-smart cocoa.